Proposed recommendations for diagnosing and managing individuals with glutaric aciduria type I: second revision. Issue 1 (16th November 2016) - Boy, Nikolas; Mühlhausen, Chris; Maier, Esther M.; Heringer, Jana; Assmann, Birgit; Burgard, Peter; Dixon, Marjorie; Fleissner, Sandra; Greenberg, Cheryl R.; Harting, Inga; Hoffmann, Georg F.; Karall, Daniela; et al.
Abstract: Glutaric aciduria type I (GA‐I; synonym, glutaric acidemia type I) is a rare inherited metabolic disease caused by deficiency of glutaryl‐CoA dehydrogenase located in the catabolic pathways of L‐lysine, L‐hydroxylysine, and L‐tryptophan. The enzymatic defect results in elevated concentrations of glutaric acid, 3‐hydroxyglutaric acid, glutaconic acid, and glutaryl carnitine in body tissues, which can be reliably detected by gas chromatography/mass spectrometry (organic acids) and tandem mass spectrometry (acylcarnitines). Most untreated individuals with GA‐I experience acute encephalopathic crises during the first 6 years of life that are triggered by infectious diseases, febrile reaction to vaccinations, and surgery. These crises result in striatal injury and consequent dystonic movement disorder; thus, significant mortality and morbidity results. In some patients, neurologic disease may also develop without clinically apparent crises at any age. Neonatal screening for GA‐I us being used in a growing number of countries worldwide and is cost effective. Metabolic treatment, consisting of low lysine diet, carnitine supplementation, and intensified emergency treatment during catabolism, is effective treatment and improves neurologic outcome in those individuals diagnosed early; treatment after symptom onset, however, is less effective. Dietary treatment is relaxed after age 6 years and should be supervised by specialized metabolic centers. The major aim of this second revision of proposed recommendations is to re‐evaluate the previous recommendations (Kölker et al. J Inherit Metab Dis 30:5‐22, 2007b; J Inherit Metab Dis 34:677‐694, 2011) and add new research findings, relevant clinical aspects, and the perspective of affected individuals.